Refining and Expanding Nonribosomal Peptide Synthetase Function and Mechanism - McErlean, Matt (J Ind Microbiol Biotechnol, 2019)
Nonribosomal peptide synthetases (NRPSs) are involved in the biosynthesis of numerous peptide and peptide-like natural products that have been exploited in medicine, agriculture, and biotechnology, among other fields. As a consequence, there have been considerable efforts aimed at understanding how NRPSs orchestrate the assembly of these natural products. This review highlights several recent examples that continue to expand upon the fundamental knowledge of NRPS mechanism and includes (1) the discovery of new NRPS substrates and the mechanism by which these sometimes structurally complex substrates are made, (2) the characterization of new NRPS activities and domains that function during the process of peptide assembly, and (3) the various catalytic strategies that are utilized to release the NRPS product. These findings continue to strengthen the predictive power for connecting genes-to-products, thereby facilitating natural product discovery and development in the Genomics Era.